Um estudo sobre a ética de Paul Ricoeur a partir de alguns de seus conceitos de origem aristotélica - Nascimento, Fernando Luís do (2009)
The main objective of this text is to present how concepts derived from Aristotle s ethics theory have been incorporated into Paul Ricoeur s practical philosophy and to raise some potential distances to such appropriation. In order to do so, this study tries to evaluate in which extent the concepts from Aristotle, specifically those described in Nichomachean Ethics, were used by Ricoeur in his ethics of ipseity, which was put together in chapters seven, eight and nine of Oneself as Another